Clarifying the Role of the Socratic Method in CBT: a Survey of Expert Opinion - Clark, G.; Egan, Sarah (Guildford Publications, 2018)
The Socratic Method is widely described as an important component in the delivery of cognitive behaviour therapy (CBT). However, there is a lack of clarity regarding the perceived role and importance of the Socratic Method in CBT. A brief questionnaire survey was completed by 15 expert CBT researchers to evaluate the perceived role and function of the Socratic Method in CBT. Survey responses were examined using thematic analysis. Results suggested that respondents believe that the Socratic Method has a number of benefits within CBT and that its effective application necessitates it being applied differentially across individuals and therapeutic tasks. A consensus was not reached amongst respondents regarding the role of the Socratic Method, with some responses describing it as a central feature of CBT whilst others identified it as a valuable adjunct to treatment which is nonessential. The implications of the findings and areas for future research are discussed.